Were Bid-Ask Spreads in the Foreign Exchange Market Excessive During the Asian Crisis? - Becker, Torbjorn (IMF Working Papers; Working Paper ;, 2005)
Bid-ask spreads for Asian emerging market currencies increased sharply during the Asian crisis. A key question is whether such wide spreads were excessive or explained by models of bid-ask spreads. Precrisis estimates of standard models show that spreads during the crisis were in most cases tighter than spreads predicted by the models and there are few cases of excessive spreads. The result is largely explained by the substantial increase in exchange rate volatility during the crisis and to some extent by the level change. The empirical models have greater explanatory power for emerging- than for mature-market currencies.